Teologi Wirausaha - Abdul Jalil (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2012)
In the social theory of religion, it is commonly believed that the inner aspect of man such as religious experience does have a role in shaping his outer, namely external dimension. How one behaves is a result of his/her inner state. One?s attitude is none other than the manifestation of his/her religiousness. On that basis, this paper argues that the spirit of entrepreneurship that one has within him/her is the result of his/her faith ?and also understanding- of his/her religion. The paper holds that it is religion that drives one to be an entrepreneur. The Islamic world-view concerning the dynamics of life for instance, has been the major source of inspiration for many youngsters to do business. This paper therefore deals with some Islamic teachings concerning life such as worldly well-being, free will and the value of work before God. The paper however also discovers that although Islam has a lot to say concerning business, only few Muslims made use of its teaching do develop what can be called Islamic entrepreneurship.??